The financing of apprenticeship training in the light of labor market regulations - Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser]; Walden, Günter [Verfasser]; Wenzelmann, Felix [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2010)
"In this paper we analyze the training behavior of firms in Germany and Switzerland — two countries with a comparable apprenticeship system but strong differences in the regulation of their respective labor markets. We make use of two representative firm-level surveys on the provision of apprenticeship training to analyze differences in the costs and benefits of training and the firm's training decision. Our results suggest that firms are more likely to make a substantial (short-term) net investment in apprenticeship training in the presence of strong employment protection laws." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 4.2 Kostenarten; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; I 2.1 Deutschland; Duales System; Ausbildungskosten; Ausbildungsertrag; Ausbildungsvergütung; Kosten-Nutzen-Relation; Ausbildungsplatzpotenzial; Ausbildungsverhalten; Beziehung Bildungssystem Beschäftigungssystem; Arbeitsmarkt; Regulierung; Internationaler Vergleich; Schweiz; Bundesrepublik Deutschland